Application of signal theory to the measurement of fluid displacement in a pipe – SIMTU System - Moreno Ascanio, Andersson Leonardo; Torres Hoyos, Miguel Ángel; Cuesta Díaz, Flavia; García Arango, David Alberto; Moreno Ascanio, Andersson Leonardo; Torres Hoyos, Miguel Ángel; Cuesta Díaz, Flavia; García Arango, David Alberto; Moreno Ascanio, Andersson Leonardo; Torres Hoyos, Miguel Ángel; Cuesta Díaz, Flavia; García Arango, David Alberto (Corporación universitaria Americana, 2021)
The application of the theory of signals to the measurement of fluid displacement shows how, through wireless signals, data can be transmitted in real time to an information system made to observe the changes that differ from said signal. The project is based on statistically measuring results of values transmitted through network devices; Likewise, it is a means of preventingfuture disasters, whether ecological or monetary. The idea of the general project is that by means of the fluids that pass and run through a pipe, they drive a propeller and this rotation allows a voltage to be generated thanks to a motor; this voltage will be transmitted from a wireless or wired device to a receiver in a computer; where the "SIMTu" information system will generate a view of the results obtained in the received data, these filesare generally numerical values and are established to givemeasurements and in this way generate adequate statistics for their previous study